The Concept and Practice of Polygamy in Islam (Multidisciplinary Journal of Thought and Research, 2025)
The concept of polygamy in Islam practiced by the Prophet is very different from the polygamy that occurs today. Today's polygamy is often practiced without proper reasons. Polygamy practiced without proper reasons can lead to negative impacts, such as violence against women, household breakdown, and child neglect. This study aims to examine the concept and practice of polygamy in Islam. This research uses a qualitative method with the type of living Quran and hadith research with data sources taken from the arguments of the Quran and hadith, the results of ijtihad, the opinions of experts. The selection of this living Quran method refers to Engkizar's theory based on the needs and objectives of the topic under study. In addition, the author also strengthens data sources from various previous research results that have been published in reputable international journals. All of the above data is analyzed thematically. The analysis shows that there are five concepts of polygamy in Islam. The five concepts are: i) Able to be fair, ii) the maximum number of wives is four, iii) must be based on benefit, iv) able to provide, v) not because of the urge of lust. This research can be used as a reference for further research on Islamic studies, especially in the field of Islamic fiqh, enriching the literature on the relationship between world activities and Islamic spirituality.